Solid phase peptide synthesis - Kent, Stephen (Henry Stewart Talks, 2008)
Chemical structure of peptides, Chemical peptide synthesis, Classical solution synthesis, Solid-phase peptide synthesis, Chemistry of SPPS, Automated solid-phase peptide synthesis, Impact of SPPS, Fundamentals of SPPS, Synthesis takes place within the beads, 'Super-elastic' swelling of peptide-resin beads, Boc chemistry SPPS, Fmoc chemistry SPPS, 'Difficult' peptide sequences in SPPS, Optimized solid-phase peptide synthesis, Impact on SPPS of modern analytical methods, Extensions of SPPS & applications of the solid-phase principle, Scope and limitations of SPPS, Impact of chemical ligation, Total synthesis of human lysozyme
Archived at 2020/08/13